Prevalence and Factors Related to Visual Impairments in Children With Bilateral Cataract Following Surgery and the Potential Need for Education and Rehabilitation Services. (January 2022) - Yahalom, Claudia; Kochavi, Moria Medezinsky; Mechoulam, Hadas; Cohen, Evelyne; Anteby, Irene
Introduction: Pediatric cataract is still a major cause for childhood visual impairment. The goal of our study was to analyze the prevalence of children with impaired vision (6/15 or worse) after surgery for bilateral cataract, to evaluate factors associated with it and to emphasize the importance for visual rehabilitation including the use of visual aids, educational measures, and social worker services. Methods: Retrospective analysis of medical records from children who underwent surgery for cataract up to age 6 years, with a follow-up of at least 4 years. Clinical characteristics retrieved from medical records included visual acuity, presence of nystagmus and/or strabismus, age at surgery, intraocular lens (IOL) implantation, and others. Results: Fifty-five children were included in the study. Follow-up ranged from 4 to 13 years (Mdn = 6.8). Visual impairment was found in 15/24 (62.5%) of children operated on before the age of 6 months (group 1), and in 7/31 (22.5%) n those operated after the age of 6 months (group 2; p = .019). Thirty-eight of the 55 children had a primary IOL implantation; nystagmus and microphthalmos were also associated with higher rates of visual impairment. Discussion: Despite early and modern surgery, long-term visual outcome remains poor in children undergoing bilateral cataract surgery at young age. When discussing visual prognosis with parents, it is important to recognize factors associated with visual impairment, such as need for surgery before age 6 months, nystagmus and microphthalmos, as well as the importance for early visual rehabilitation services when needed. Implications for Practitioners: Our study aims to highlight the high number of children left with visual impairment and blindness following modern and timely treatment for early cataract. Early referral for visual rehabilitation will optimize quality of life in these children and will probably allow a wider range of opportunities as adults.